COCONUT SEED GARDENS: A REVIEW - D.V. Liyanage (International Coconut Community, 1988)
Coconut Seed Gardens are necessary for the mass production of improved coconut cultivars.They will play a dominant role in dvelopment programmes until tissue culture creates new plants. Models of seed gardens developed in Sri Lanka, Indonesia and Ivory Coast are outlined. The differences between them with regard to structure and management are enumerated.